Social Media Effectiveness as a Promotional Medium to Increase Sales Volume - Titi Andriyani; M Syahirman Yusi; Yusnizal Firdaus (Jurnal Aplikasi Manajemen dan Bisnis, 2022)
This study aims to determine the effectiveness of social media as a promotional medium in increasing sales volume using the AISAS Model at the Return Space and Coffee Cafe in Palembang. Research time was 6 month. The research method was descriptive quantitative and qualitative research with a questionnaire method. Results: The AISAS variables with the indicator of "sharing information" had the lowest IS score of 76.2%, with a "strong" score interpretation, while the "interest" indicator received the highest score of 87.2%, with a "very strong" score interpretation. The sales volume variable with the "Promotion" indicator obtained the lowest IS score of 82.4%, with a "very strong" score interpretation, and the "product" indicator received the highest IS score of 86.8%, with a "very strong" score interpretation. Conclusions: The effectiveness of social media used by the Return Space and Coffee Café in Palembang has not appropriately been executed since the lack of posts or content uploaded on the Instagram and TikTok platforms, which has led to customers giving poor ratings to the use of promotional mediums using digital media. As for the sales volume with the "promotion" indicator, it receives the lowest score since it relates to the Return Cafe's very seldom use of digital media, making customers less aware of their promotions to attract customers to this Café.